Blends of cross-linked high amylose starch/pectin loaded with diclofenac - Soares, Grazielle Arantes [UNESP]; Castro, Ana Doris de [UNESP]; Cury, Beatriz S.F. [UNESP]; Evangelista, Raul Cesar [UNESP] (Elsevier, 2013)
Polymers blends represent an important approach to obtain materials with modulated properties to reach different and desired properties in designing drug delivery systems in order to fulfill therapeutic needs. The aim of this work was to evaluate the influence of drug loading and polymer ratio on the physicochemical properties of microparticles of cross-linked high amylose starch-pectin blends loaded with diclofenac for further application in controlled drug delivery systems. Thermal analysis and X-ray diffractograms evidenced the occurrence of drug-polymer interactions and the former pointed also to an increase in thermal stability due to drug loading. The rheological properties demonstrated that drug loading resulted in formation of weaker gels while the increase of pectin ratio contributes to origin stronger structures. © 2012 Elsevier Ltd.
Keywords: High amylose starch; Pectin; Polymer blends; Rheology; Thermal analysis; X-ray diffraction; Controlled drug delivery systems; Diclofenac; Drug delivery system; Drug loading; Drug-polymer interaction; High amylose; Micro-particles; Physicochemical property; Rheological property; X-ray diffractograms; Controlled drug delivery; Crosslinking; Functional polymers; Materials properties; Starch; Thermoanalysis; X ray diffraction; Loading; amylose; diclofenac; drug carrier; microsphere; pectin; chemistry; flow kinetics; particle size; temperature; Amylose; Drug Carriers; Microspheres; Particle Size; Pectins; Temperature